APLIKASI SISTEM INFORMASI PENJUALAN DAN PEMBELIAN PADA UNIT USAHA SWALAYAN PRIMER KOPERASI DARMA PUTRA UJWALA MALANG - Putri Ulfiyah; Weda Adistianaya Dewa; Andri Prasetyo (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2024)
Primkop Darma Putra Ujwala is an extra weight of structural units that constitute the chain Pangkostrad Puskopad. Darma Putra Ujwala has two types, namely savings and loan business and self-service business unit. self-service business unit aims to support the welfare and provide facilities for providers of daily necessities to all Pangkostrad soldiers and their families. The purpose of this research is terbangunya information systems sales and purchases on the primary self-service business unit cooperative darma Ujwala son. The method applied in this study is developing a system Software Development Life Cycle (SDLC). The results of this study can be used to give information supplies inventory, facilitate service sales and purchases, making reports both buying and selling daily, monthly and yearly. In the sales report can be used to print the bill of sale in addition to the reports the bill in cash and debt. Tagian report will be taken into account to deduct the salary of each member.